Social Criticism and Class Representation of the People in the Novel Zuqaq Al – Midaq by Naguib Mahfouz: A Study of Literary Sociology - Ilmi, Bachrotul (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
This study examines social criticism and the representation of the working class in Naguib Mahfouz’s novel Zuqaq al-Midaq (Midaq Alley). The primary focus of the study is the pressures of colonialism and structural poverty in 1940s Cairo, which forced the working class to make moral compromises in order to survive. The approach used is qualitative, employing a literary sociology paradigm and drawing on theories of reflection and social dialectics. Data were collected through a literature review, while data analysis was conducted using content analysis techniques to examine the narratives, dialogues, and behaviors of the main characters, such as Hamida, Kirsha, Abbas, and Husniya, as representations of their social classes. The research findings indicate that Zuqaq al-Midaq represents a microcosm of the systemic failure of Egyptian society in confronting the transition to modernity. Mahfouz sharply captures the dehumanization of the working class, where poverty is no longer merely an economic issue but the primary factor eroding ethical and humanitarian values. Specific findings reveal that the character Hamida chooses prostitution as a false escape from poverty, while Abbas experiences total disillusionment due to the false promise of modernity. Furthermore, the character Kirsha represents the moral hypocrisy that thrives amidst economic pressure. This study also finds that British colonialism not only exploited the community economically but also disrupted the social and psychological fabric of the alley’s residents. Thus, Mahfouz delivers a scathing critique of class inequality that creates a vicious cycle of suffering for the lower classes. The implications of this study underscore that literature serves a didactic-critical function in voicing the realities of marginalized groups often overlooked by grand historical narratives, while simultaneously serving as a critical mirror for modern readers regarding the dangers of structural injustice.